The tradedy of woman's emancipation - Goldman, Emma (New York: Mother Earth Publishing Association, 1911)
"Emma Goldman DIGITAAL TE RAADPLEGEN IN DE LEESZAALUit : Anarchism and Other Essays’ / Emma Goldman .- Second Revised Edition. .- New York & London: Mother Earth Publishing Association, 1911"